Pengaruh Lingkungan Keluarga dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa FKIP UNS Dimoderasi Peran Program Studi - Arinie Hudaya; Leny Noviani; Khresna Bayu Sangka (Universitas Negeri Surabaya, 2023)
This study aims to determine the influence of the family environment and entrepreneurship education partially affect the interest in entrepreneurship and the role of the study program in strengthening the influence on the entrepreneurial interest of FKIP UNS students. This research is a quantitative method research. The population in this study is active students of FKIP UNS batch 2018-2020. The sampling technique in this study was proportionate random sampling with a sample of 400 respondents. Through the Moderated Regression Analysis (MRA) hypothesis test, the results showed (1) family environment (2) entrepreneurship education has a positive and significant influence on entrepreneurial interest. Then, (3) the role of the study program was found not to be a moderator variable so that it did not have a moderating effect so that this variable could not strengthen the influence of the family environment on entrepreneurial interest. In addition, (4) the role of the study program was found to have the nature of weakening the influence of entrepreneurship education on entrepreneurial interest.